Organophotoredox-Catalyzed C–H Alkylation of Imidazoheterocycles with Malonates: Total Synthesis of Zolpidem - Chaubey, Narendra R.; Kapdi, Anant R.; Maity, Biswanath (Synthesis, 2020)
Organophotocatalytic C–H bond functionalization has attracted a lot of attention in the past several years due to the possibility of catalyzing reactions in a metal- and peroxide-free environment. Continuing on these lines, an organophotoredox-catalyzed C–H functionalization of imidazo[1,2-a]pyridines and related heterocycles with bromomalonates under mild conditions is reported, providing excellent yields of the products at room temperature. This is the first report involving malonates as coupling partners leading to the synthesis of a range of functionalized products including total synthesis of zolpidem, a sedative-hypnotic drug molecule.
Keywords: organophotoredox; C–H functionalization; imidazoheterocycles; zolpidem; drug prejudice